Morphological and Filtration Performance Studies of Alumina Disc Membranes - Nazihah Che Abdul Rahim, Azzah; Sailah Sihar, Ainun; Zaman Shahruddin, Munawar; Hashimah Alias, Nur; Nurliyana Che Mohamed Hussein, Siti; Fazril Irfan, Mohd; Hidayati Othman, Nur (International Journal of Engineering and Technology, 2018)
Ceramic membranes can be used for water separation and gas filtration owing to its chemical inertness, good mechanical and porous properties. In this work, a total of 18 ceramic membranes were fabricated by varying the parameters such as ceramic powder composition (Al2O3), solvent (DMSO) concentration in external coagulation bath, and sintering time. The morphologies of the prepared alumina disc membranes prepared were studied using digital microscope. In order to understand the effects of morphologies toward the permeation rate of the ceramic membranes-dead end water permeation tests and salt rejection tests were carried out to study the performance of the alumina disc membranes. Membrane 1 which was fabricated with 50% alumina loading, 0% DMSO in coagulant and sintering time of 8h was used as reference membrane. It was found that by increasing the alumina up to 65%, the structure become denser and water fluxÂ  decreased up to 26%, while the salt rejected increased by 55%. Effect of increasing the solvent concentration in external coagulation bath was obvious in finger length which becomes shorter and performed 61% but fluctuates in salt rejection. Sintering time effect was not significant in salt rejection studies as it gives only small difference but increase in water flux because the longer sintering time caused void to the membrane. Different results were shown and proven with varied parameters such as alumina loading, DMSO concentration and sintering time.Â Â